Pengaruh Social Media Marketing Instagram dan Celebrity Endorser terhadap Minat Beli Konsumen: Studi pada Fashion Store Laxmii Id di Denpasar - Pramesti, Kadek Diah Chandra; Trarintya, Mirah Ayu Putri; Mahayasa, I Gede Aryana (Media Bisnis, 2024)
This study aims to determine the influence of social media marketing, Instagram, and celebrity endorsers on buying interest. This research was conducted at the Fashion Store Laxmii Id in Denpasar using the purposive sampling method with a sample of 100 people. Primary data collection was carried out using a questionnaire. The data analysis techniques used were classical assumption test, multiple linear regression analysis, partial significance test (t-test), and simultaneous significance test (f-test). The results of the analysis show that 1) Instagram social media marketing has a positive and significant effect on consumer buying interest, 2) celebrity endorsers have a positive and significant effect on consumer buying interest, 3) Social media marketing, Instagram, and celebrity endorsers have a positive and significant effect on consumer buying interest. The advice that can be given is that Laxmii Id in Denpasar is expected to increase the activeness of Instagram social media as an advertising medium and then use an endorser who is better known by many people or a celebrity who has a positive image in the minds of consumers.